Life and death of Vladimir Mikhailovich Bekhterev - Péricles Maranhão Filho; Eliana Teixeira Maranhão; Eliasz Engelhardt (Arquivos de Neuro-Psiquiatria)
Vladimir Mikhailovich Bekhterev was a Russian innovative neuroscientist, extraordinary in the study, diagnosis, and research in the fields of neurology, psychology, morphology, physiology, and psychiatry. Considering the ample and multifaceted scientific feats, only some are touched in a very brief manner. However, it is necessary to highlight his contributions to neurology, with the description of structures, signs and syndromes, to physiology, including reflexology, which later underpinned behaviorism, to psychology, including objective psychology and suggestion. His accomplishments and legacy remained until the present days. Some comments about the scenery that involved his death are also presented.